2015
DOI: 10.1002/2014ja020330
|View full text |Cite
|
Sign up to set email alerts
|

Topside ionospheric irregularities as seen from multisatellite observations

Abstract: We use in situ data from CHAMP and DMSP satellites, along with data of GPS receiver onboard CHAMP satellite and ground-based GPS receivers to study the occurrence and global distribution of ionospheric irregularities during the main phase of the geomagnetic storm of 29-31 August 2004 (minimum Dst excursion of À128 nT). Using the CHAMP GPS measurements, we created maps of GPS phase fluctuation activity and found two specific zones of the most intense irregularities: (1) the region of the auroral oval at high la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…Ionospheric effects of energetic particles, which can penetrate to the D, E, and F ionospheric regions from magnetosphere and interplanetary space, have been known for a long time as well as are studied now (e.g., Abdu et al, 1998;Suvorova et al, 2012Suvorova et al, , 2013Suvorova et al, , 2014Zigman et al, 2014;Zakharenkova and Astafyeva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric effects of energetic particles, which can penetrate to the D, E, and F ionospheric regions from magnetosphere and interplanetary space, have been known for a long time as well as are studied now (e.g., Abdu et al, 1998;Suvorova et al, 2012Suvorova et al, , 2013Suvorova et al, , 2014Zigman et al, 2014;Zakharenkova and Astafyeva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Even more rare events are occurrences of intensive ionospheric irregularities and/or plasma bubbles in the predawn sector. Those were occasionally observed at the recovery phase of magnetic storms [e.g., Yeh et al , ; Li et al , ; Zakharenkova and Astafyeva , ; Zakharenkova et al , ] or even under geomagnetically quiet and during solar minimum conditions [ de la Beaujardière et al , ; Dao et al , ; Gentile et al , ]. The results from Communications/Navigation Outage Forecasting System (C/NOFS) satellite suggested that during geomagnetically quiet conditions, a passage of the solar terminator and the associated upward plasma drifts can serve as a source of such irregularities [ de la Beaujardière et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…ROTI maps presented for the dusk/nighttime sector in Figure follows a similar presentation of the TEC maps shown in Figure . The ionospheric irregularities are prevalently nighttime events, although there had been reported cases of initiation and enhancement of ionospheric irregularities in the dawn/morning sector due to geomagnetic storm impact (Fukao et al, ; Li et al, ; Zakharenkova & Astafyeva, ). The ionospheric irregularities were quite remarkable at the nighttime during the two main phases of the storm on 8 September which were not observed on the other days (see Figures a–d).…”
Section: Observationsmentioning
confidence: 99%